Sacroiliac radiographic progression in recent onset axial spondyloarthritis - Dougados, Maxime (2017)
Funding Information: Acknowledgements the dESIr cohort was sponsored by the département de la recherche Clinique et du développement de l’Assistance publique–Hôpitaux de paris. this study is conducted under the umbrella of the French Society of rheumatology and InSErM (Institut national de la Santé et de la recherche Médicale). the database management is performed within the department of epidemiology and biostatistics (professor paul Landais, d.I.M., nîmes, France). An unrestricted grant from pfizer was allocated for the 10 years of the follow-up of the recruited patients. the authors would like to thank the different regional participating centres: pr Maxime dougados (paris – Cochin B), pr André Kahan (paris - Cochin A), pr olivier Meyer (paris - Bichat), pr pierre Bourgeois (paris - La pitié Salpetrière), pr Francis Berenbaum (paris - Saint Antoine), pr pascal Claudepierre (Créteil), pr Maxime Breban (Boulogne Billancourt), dr Bernadette Saint-Marcoux (Aulnay-sous-Bois), pr philippe Goupille (tours), pr Jean-Francis Maillefert (dijon), dr xavier puéchal, dr Emmanuel dernis (Le Mans), pr daniel Wendling (Besançon), pr Bernard Combe (Montpellier), pr Liana Euller-Ziegler (nice), pr philippe orcel, dr pascal richette (paris - Lariboisière), pr pierre Lafforgue (Marseille), dr patrick Boumier (Amiens), pr Jean-Michel ristori, pr Martin Soubrier (Clermont-Ferrand), dr nadia Mehsen (Bordeaux), pr damien Loeuille (nancy), pr rené-Marc Flipo (Lille), pr Alain Saraux (Brest), pr Corinne Miceli (Le Kremlin Bicêtre), pr Alain Cantagrel (toulouse), pr olivier Vittecoq (rouen). the authors would also like to thank UrC-CIC paris Centre for the coordination and monitoring of the study. Contributors All authors contributed and finally approved the current manuscript. Competing interests none declared. Patient consent obtained. ethics approval Comitte de protection des personnes Ile de France III. Provenance and peer review not commissioned; externally peer reviewed. Open Access this is an open Access article distributed in accordance with the Creative Commons Attribution non Commercial (CC BY-nC 4.0) license, which permits others to distribute, remix, adapt, build upon this work non-commercially, and license their derivative works on different terms, provided the original work is properly cited and the use is non-commercial. See: http://creativecommons.org/ licenses/by-nc/4.0/ © Article author(s) (or their employer(s) unless otherwise stated in the text of the article) 2017. All rights reserved. no commercial use is permitted unless otherwise expressly granted. Publisher Copyright: © Article author(s) (or their employer(s) unless otherwise stated in the text of the article) 2017. All rights reserved.